Inclusion and Exclusion in Political Discourse: Deixis in Barrack Obama’s Speeches - Wiwik Yully Widyawati (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
This study examines the use of deixis for personal, spatial, and temporal anchorage of political discourse. Using two thematically and contextually different speeches of obama as its database., the paper recognize how politicians can associate with and dissociate from actions taken by them or their officer at different time. I conclude by locating some of antics of political leaders to conscript their subjects into accepting their views on conversial issues or position. Key word: inclusion and exclusion, political discourse, deixis